BELEIDSREGEL SEBAGAI INSTRUMEN PERLINDUNGAN WARGA NEGARA DALAM UPAYA PELESTARIAN SATWA - Kadek Cahya Susila Wibawa; Shania Prilla Davanti; F.C. Susila Adiyanta (Faculty of Law, Universitas Gadjah Mada, 2023)
Abstract Consequences of the stipulation of Permenlhk No. 20 of 2018 is the shift in the classification of some animals that were not protected before to become protected. Beleidsregel is a logical consequence of the usage of discretion in the government administration in a welfare state. The realization of public welfare as the main goal of a welfare state can be accomplished by recognizing discretion. Beleidsregel is needed if there is any urgent problem that requires immediate solution, including the efforts of animals conservation that intersect the interest of citizens who exploit protected animals that are unprotected before. Beleidsregel issued by agencies within the Ministry of Environment and Forestry, namely the Circular Letter of the General Director of Natural Resources and Ecosystem Conservation and the Announcements of the Central Java Natural Resources Conservation Agency, has provided legal certainty regarding the transition required in the classification change of unprotected animals into protected animals. The Circular Letter has instructed the Natural Resources Conservation Agencies to collect data and tag the protected animals, while the Announcements has provided informations regarding provisions of protected animals data collection during the COVID-19 pandemic to reduce the transmission of COVID-19. Abstrak Konsekuensi penetapan Permenlhk No. 20/2018 adalah beralihnya penggolongan beberapa satwa yang semula tidak dilindungi menjadi dilindungi. Beleidsregel adalah konsekuensi logis penggunaan asas diskresi dalam penyelenggaraan pemerintahan di negara kesejahteraan. Perwujudan kesejahteraan umum yang menjadi tujuan utama negara kesejahteraan dapat terakomodir dengan adanya pengakuan asas diskresi. Beleidsregel dibutuhkan apabila terjadi persoalan yang mendesak di masyarakat dan membutuhkan penyelesaian yang segera, termasuk dalam upaya pelestarian satwa yang bersinggungan dengan kepentingan warga negara pemanfaat satwa yang semula tidak dilindungi menjadi dilindungi. Beleidsregel yang dikeluarkan oleh instansi yang berada di lingkup Kementerian Lingkungan Hidup dan Kehutanan, yaitu SE Dirjen Konservasi Sumber Daya Alam dan Ekosistemnya serta Pengumuman Balai Konservasi Sumber Daya Alam Jawa Tengah, telah memberikan kepastian hukum dengan perihal peralihan yang dibutuhkan dalam perubahan penggolongan satwa menjadi satwa yang dilindungi. SE telah menginstruksikan kepada Balai/Balai Besar Konservasi Sumber Daya Alam untuk melakukan pendataan dan penandaan satwa, sedangkan Pengumuman telah memberikan informasi perihal ketentuan pendataan satwa di masa pandemi COVID-19 untuk mengurangi penyebaran COVID-19.